An Analysis of English Teachers' Online Teaching Strategies during Covid-19 Pandemic - Balqis Yury Shakina; Sahril Nur; La Sunra (Journal of Excellence in English Language Education, 2022)
This research aims to describe and find out the two following objects: (1) the English teachers' online teaching strategies, and (2) The strategies help the teachers’ in online teaching. This research used Qualitative model. The instrument collecting data were online class observation and interview. In order to get the sample, the researchers used random sampling technique. There were 3 English teachers in SMAN 5 Makassar as the sample of this research. The results of the research indicated that (1) teachers used cooperative learning and discovery-based learning in online teaching during the Covid-19 pandemic era. (2) Cooperative learning and discovery-based learning can help teachers teach. Cooperative learning strategies help the teachers in teaching English because the students can know about the importance of group study. Discovery-based learning strategies help the teacher in teaching English because with the students can more explore knowledge in another resources. According to the results of the research, it can be concluded that the teacher’s strategies in online teaching during the pandemic there are Cooperative learning and Discovery Based Learning.